Feasibility Analysis of Tempe Business in Peunaga Pasie Village, Meureubo District, West Aceh Regency (Case Study of UD Tempe Mawar) - Aulia, Muhammad Reza; Nisa, Al Qoridatul; Fuqara, Fantashir Awwal; Muzammil, Abdul; Bagio, Bagio (Yayasan Gema Bina Nusantara, 2024)
The number of tempeh industries in West Aceh Regency continues to decrease every year. From 2021 to 2023, the number of tempeh industry units continues to decline annually, reaching just 21. One of the issues identified in this study pertains to raw materials that frequently rot or become unsuitable for use, as well as the management of raw material supply and production costs. Specifically, unstable soybean prices, particularly when the rupiah is weak, can lead to an increase in the price of imported soybeans. This, in turn, can lead to an increase in production costs, thereby reducing the income generated. This study aims to determine how much income is generated by the owner of Mawar tempeh and to see the feasibility of the business using the Net Present Value (NPV), Internal Rate of Return (IRR), Gross Benefit Cost Ratio (Gross B/C), and Payback Period (PP) methods, and determine sensitivity analysis. Based on the results of the research that has been conducted in Meuruebo District, West Aceh Regency, based on the formulation of the problem in this study, several conclusions were drawn that the income generated is greater than the expenses incurred, and from the feasibility analysis, it shows that the results obtained by the owner of Mawar tempeh are feasible to be run or attempted, and sensitivity analysis in terms of increasing raw material prices.